Synthesis and Characterization of Some Inorganic Compounds and Study their Effect in activity of Laccase Produced by Fungal isolate Pleurotus ostreatus - Alias, M .F.; Hashim, A.J .; Kareem, T . A . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
, The new ligand(OBTMRZ),Bis[4-phenyl-3(2-propenyl)thio-1,2,4- triazole -5yl] methane was prepared and characterized by vibrational , spectra and J>hysical methods,selected metals,which were Cu11 Zn 11 Mn11,Co11,Fe" and Hg11 were reacted with ligand to produce new complexes.Solid compounds were isolated and identified through metal analysis.vibrational and electronic spectra,molar conductivity magnetic susceptibility measurements and other techniques depending on the data obtained,chemical formula geometry of complexes were suggested. Other ligands(OXH,TRZH,OTRZ,BTMRZH2)were prepared and select metals(Cu",znnandMn11)reacted with them to produce complexes. These complexes were characterized by infrared spectroscopy and physical methods . Laccase was produce from fungal isolate P .ostreatus using submerge culture at 30C0 pH =6.5 after 96 hour of incubation .The analysis of fungal filtrate using (HPLC) technique shown the presence one peak which indicated , that was partial purifioo , the flam atomic ab orption technique indicated that the enzyme was contains (2Zn,